3D Harmonic and Subharmonic Imaging for Characterizing Breast Lesions: A Multi‐Center Clinical Trial. (25th October 2021) - Forsberg, Flemming; Piccoli, Catherine W.; Sridharan, Anush; Wilkes, Annina; Sevrukov, Alexander; Ojeda‐Fournier, Haydee; Mattrey, Robert F.; Machado, Priscilla; Stanczak, Maria; Merton, Daniel A.; Wallace, Kirk; Eisenbrey, John R.
Abstract : Objective: Breast cancer is the most frequent type of cancer among women. This multi‐center study assessed the ability of 3D contrast‐enhanced ultrasound to characterize suspicious breast lesions using clinical assessments and quantitative parameters. Methods: Women with suspicious breast lesions scheduled for biopsy were enrolled in this prospective, study. Following 2D grayscale ultrasound and power Doppler imaging (PDI), a contrast agent (Definity; Lantheus) was administrated. Contrast‐enhanced 3D harmonic imaging (HI; transmitting/receiving at 5.0/10.0 MHz), as well as 3D subharmonic imaging (SHI; transmitting/receiving at 5.8/2.9 MHz), were performed using a modified Logiq 9 scanner (GE Healthcare). Five radiologists independently scored the imaging modes (including standard‐of‐care imaging) using a 7‐point BIRADS scale as well as lesion vascularity and diagnostic confidence. Parametric volumes were constructed from time‐intensity curves for vascular heterogeneity, perfusion, and area under the curve. Diagnostic accuracy was determined relative to pathology using receiver operating characteristic (ROC) and reverse, step‐wise logistical regression analyses. The κ‐statistic was calculated for inter‐reader agreement. Results: Data were successfully acquired in 219 cases and biopsies indicated 164 (75%) benign and 55 (25%) malignant lesions. SHI depicted more anastomoses and vascularity than HI ( P < .021), but there were no differences by pathology ( P > .27). Ultrasound achieved accuracies of 82 to 85%, which was significantly better than standard‐of‐care imaging (72%; P < .03). SHI increased diagnostic confidence by 3 to 6% ( P < .05), but inter‐reader agreements were medium to low (κ < 0.52). The best regression model achieved 97% accuracy by combining clinical reads and parametric SHI. Conclusions: Combining quantitative 3D SHI parameters and clinical assessments improves the characterization of suspicious breast lesions.